Implementasi Peraturan Bupati Probolinggo No. 07 Tahun 2020 Dalam Program (RTLH) Program Rehabilitasi Rumah Tidak Layak Huni Studi Pada Kecamatan Kuripan Probolinggo - Marwiyah, Siti; Rahmadi, Andhi Nur; Rizki, M. Fathur (Universitas Jabal Ghafur, 2025)
This study aims to evaluate the implementation of Probolinggo Regent Regulation No. 07 of 2020 related to the rehabilitation program for uninhabitable houses (RTLH) in Kuripan District. The background of this research arises from the urgency to improve housing conditions that are suitable for the community, considering that many houses still do not meet health and safety standards. The method applied in this research is a qualitative approach, involving 15 informants consisting of government officials, beneficiaries, and local community leaders. The data analysis technique used is thematic analysis, which allows the researcher to identify and categorize the main themes from the data obtained through interviews and observations. The research findings indicate that the success of the RTLH rehabilitation program is influenced by several factors, including community participation, availability of resources, and the existing bureaucratic structure. Although there have been some achievements in the RTLH rehabilitation, challenges related to inter-agency coordination and budget limitations remain significant obstacles. The conclusion of this study recommends that local governments enhance communication and collaboration among agencies, as well as encourage more active community participation at every stage of the program. Additionally, the importance of periodic evaluations to adjust the program to the evolving needs of the community is also emphasized.Keywords: Implementation, Regent Regulation, rehabilitation